Compositional Differences in the Oral Microbiome of E-cigarette Users - Chopyk, Jessica; Bojanowski, Christine M.; Shin, John; Moshensky, Alex; Fuentes, Ana Lucia; Bonde, Saniya S.; Chuki, Dagni; Pride, David T.; Crotty Alexander, Laura E. (Frontiers in Microbiology, 2021)
Electronic (e)-cigarettes have been advocated as a safer alternative to conventional tobacco cigarettes. However, there is a paucity of data regarding the impact of e-cigarette aerosol deposition on the human oral microbiome, a key component in human health and disease. We aimed to fill this knowledge gap through a comparative analysis of the microbial community profiles from e-cigarette users and healthy controls (non-smokers/non-vapers, NSNV). Moreover, we sought to determine whether e-cigarette aerosol exposure via vaping induces persistent changes in the oral microbiome. To accomplish this, salivary and buccal mucosa samples were collected from e-cigarette users and NSNV controls, with additional oral samples collected from e-cigarette users after two weeks of decreased use. Total DNA was extracted from all samples and subjected to PCR amplification and sequencing of the V3-V4 hypervariable regions of the 16S rRNA gene. Our analysis revealed several prominent differences associated with vaping, specific to the sample type (i.e. saliva, buccal). In the saliva, e-cigarette users had a significantly higher alpha diversity (Observed OTUs, Faith’s PD) compared to NSNV controls, which declined with decreased vaping. The buccal mucosa swab samples were marked by a significant shift in beta diversity between e-cigarette users and NSNV controls. There were also significant differences in the relative abundance of several bacterial taxa, with a significant increase in Veillonella and Haemophilus in e-cigarette users. In addition, nasal swabs demonstrated a trend towards higher colonization rates with Staphylococcus aureus in e-cigarette users relative to controls (19% vs. 7.1%; p = n.s.). Overall, these data reveal several notable differences in the oral microbiome bacterial community composition and diversity in e-cigarette users as compared to NSNV controls.